A randomized, placebo-controlled pilot trial of armodafinil for fatigue in patients with gliomas undergoing radiotherapy. Issue 6 (21st February 2016) - Lee, Eudocia Q.; Muzikansky, Alona; Drappatz, Jan; Kesari, Santosh; Wong, Eric T.; Fadul, Camilo E.; Reardon, David A.; Norden, Andrew D.; Nayak, Lakshmi; Rinne, Mikael L.; Alexander, Brian M.; Arvold, Nils D.; et al.
Abstract: Background: Fatigue is common among glioma patients undergoing radiotherapy (RT) and impacts quality of life (QOL). We evaluated whether armodafinil, a wakefulness-promoting medication, improves fatigue in glioma patients undergoing RT. Methods: Eligibility criteria included age ≥18 years, Karnofsky performance status ≥60, and grade 2–4 glioma undergoing RT to a total dose of 50–60 Gy. Patients were randomized 1:1 to armodafinil or placebo for 8 weeks beginning within 10 days of starting RT. Fatigue and QOL were assessed at baseline, day 22, day 43, and day 56 with the Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-F), the Functional Assessment of Cancer Therapy – General (FACT-G), the Brief Fatigue Inventory (BFI), and the Cancer Fatigue Scale (CFS). The primary aim was to detect a difference in the 42-day change in FACIT-F fatigue subscale between the 2 groups using a 2-sample Wilcoxon statistic. Results: We enrolled 81 patients total (42 armodafinil and 39 placebo). Armodafinil did not significantly improve fatigue or QOL based on the 42-day change in FACIT-F fatigue subscale, FACT-G, CFS, or BFI. Further analysis suggests no difference between the arms even after accounting for the potential bias of missing data. Treatment was well tolerated with few grade 3 or 4 toxicities. Conclusions: While treatment was well-tolerated, an 8-week course of armodafinil did not improve fatigue or QOL in glioma patients undergoing RT in this pilot study. Further studies are needed to determine whether pharmacologic treatment improves fatigue in glioma patients undergoing RT.